2008
DOI: 10.1093/eurheartj/ehm556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and sex on carotid intima-media thickness, elasticity and brachial endothelial function in healthy adults: The Cardiovascular Risk in Young Finns Study

Abstract: Reference values produced in the present study can be utilized in the cardiovascular risk stratification among young people. Sex differences in the markers of subclinical atherosclerosis were mostly explained by differences in risk factors and vessel size. This emphasizes the importance of risk factor control in the prevention of atherosclerosis in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

30
112
6
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 35 publications
30
112
6
1
Order By: Relevance
“…First, the baseline diameter of the brachial artery has been reported as one of the major determinants of FMD (4,15), and it has even been suggested as a marker to predict future cardiovascular events similar to FMD (19). In the present study, the baseline diameter of the brachial artery also had a significant correlation with FMD (r= −0.45, p< 0.01).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…First, the baseline diameter of the brachial artery has been reported as one of the major determinants of FMD (4,15), and it has even been suggested as a marker to predict future cardiovascular events similar to FMD (19). In the present study, the baseline diameter of the brachial artery also had a significant correlation with FMD (r= −0.45, p< 0.01).…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, previous large-cohort studies to assess the relationship of FMD to CVD risk factors showed age heterogeneity in the subjects. For example, the Young Finns Study was conducted in subjects aged 24-39 years (4,7), the PIVUS study and Cardiovascular Health Study were con- ducted in elderly subjects (5,9), most study subjects in the Framingham study were aged over 50 years (6) and the subjects in Celermajer's study were relatively young and included children (mean age= 36 years) (10). Thus, it has not been fully clarified whether aging itself may affect the relationships of other CVD risk factors to FMD.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous reports that blacks showed greater mean and maximum IMT than South Asians and whites after adjusting for traditional CV risk factors 21, 23. There were no significant differences between males and females except that IMT_mean_r was higher in males.…”
Section: Discussionsupporting
confidence: 92%
“…These studies reported IMT range between 0.49 and 0.59 mm for mean IMT and between 0.61 and 0.63 mm for maximum IMT 21, 22…”
Section: Discussionmentioning
confidence: 96%
“…The early increase in IMT reflects the ongoing adaptive/maladaptive process to elevated intravascular shear stress (28). Several anthropometric and metabolic findings such as age, elevated blood pressure, central obesity, hyperlipidemia, and IR have been shown as independent determinants of IMT in different populations (29)(30)(31). In a past study concerning CIMT in AI (26) it was demonstrated that in patients with non-functioning AI, a significant increase of CIMT was observed compared with BMI -unmatched subjects, while the increase was not statistically significant when compared to BMI matched controls.…”
Section: Discussionmentioning
confidence: 99%